Concrete technology - Neville, A M; Brooks, J J (NOIDA: Pearson, 2019)
About the book: The classic textbook and reference guide to concrete is updated to include the latest standards and developments. This book gives students a thorough understanding of all aspects of concrete technology from principles. An excellent coursebook for all students of Civil Engineering, Structural Engineering and Building at degree or diploma level, Concrete Technology will also be a valuable reference book for practicing engineers in the field.
Keywords: Civil Engineering; Concrete as a structural material; Aggregate; Elasticity and creep; Resistance to freezing and thawing; Lightweight concrete